A comparison of neutrophil-lymphocyte ratio and body fat percentage in hashimoto’s disease induced hypothyroid patients (Annals of Medical Research, 2021)
Aim: Inflammatory mechanisms are activated when the body mass index is increased and in cases of Hashimoto’s Thyroiditis (HT). The neutrophil-lymphocyte ratio (NLR), which is used as a new and easily accessible inflammatory marker, may be related to the body mass index. The objective of this study is to compare the NLR and body fat percentage in patients with Hashimoto’s disease induced hypothyroidism.Material and Methods: The study consisted of 29 patients diagnosed with HT induced hypothyroidism based on the clinical and laboratory findings. The control group consists of 29 healthy individuals who do not suffer from any disease known to increase TSH level. Body analysis is performed for all cases that are included in the study, and the height, weight, body fat percentage, lean body mass, visceral adiposity, basal metabolic rate, and body fluid percentages are calculated, and complete blood count, TSH, FT3, FT4, Anti-TPO tests were performed following 3-4 cc venous blood sample collection from all cases.Results: There were not any significant difference between the patient and control group in terms of gender, BMI, body fat percentage, lead body mass, visceral adiposity, fluid percentage, and basal metabolic rate data (p>0.05). NLR rate was 1.95±1.37 in patient group and 2.52±1.40 in control group. Significant difference was identified in NLR (p=0.025), fat percentage (p=0.002), lean mass (p=0.002) and visceral adiposity data (p=0.006) between the HT patients and control group when the male patients were removed from the groups. NLR was identified statistically significantly low in the patient group when compared to the control group (p0.012). There was no significant correlation between NLR and lean mass, TSH, BMI, visceral adiposity, fluid percentage, and age parameters in both groups.Conclusion: NLR, like other common inflammatory markers, is an inexpensive and easily accessible marker that can be used in hospitalized patients. However, it would be more appropriate to evaluate the conditions that may have effects on the results such as patients drug use and bone marrow suppression. It can be said that more evidence is needed to use NRL as a marker for HT management.